Genetic architecture of plant height in maize phenotype‐selected introgression families. Issue 4 (28th June 2016) - Abdel‐Ghani, Adel H.; Hu, Songlin; Chen, Yongsheng; Brenner, Everton A.; Kumar, Bharath; Blanco, Michael; Lübberstedt, Thomas
Abstract: This study aimed at developing, characterizing and evaluating two maize phenotypic‐selected introgression libraries for a collection of dominant plant height (PHT)‐increasing alleles by introgressing donor chromosome segments (DCS) from Germplasm Enhancement of Maize (GEM) accessions into elite inbred lines: PHB47 and PHZ51. Different backcross generations (BC1 ‐BC4 ) were developed and the tallest 23 phenotype‐selected introgression families (PIFs) from each introgression library (PHB47 or PHZ51) were selected for single nucleotide polymorphism genotyping to localize DCS underlying PHT. The result shows that most PIFs carrying DCS were significantly ( α = 0.01) taller than the respective recurrent parent. In addition, they contained larger donor genome proportions than expected in the absence of selection or random mating across all BC generations. The DCS were distributed over the whole genome, indicating a complex genetic nature underlying PHT. We conclude that our PIFs are enriched for favourable PHT‐increasing alleles. These two libraries offer opportunities for future PHT gene isolation and allele characterization and for breeding purposes, such as novel cultivars for biofuel production.